Effect Of Compensation And Communication On Employee Performance Of PT. Metra Palma Api (Medco Agro) - Suharno Pawirosumarto; Farida Affaandi (International Journal of Artificial Intelligence Research, 2022)
The research was conducted with the aim of knowing the effect of compensation and communication on performance at PT. Api Metra Palma (Medco Agro). The research was conducted by distributing questionnaires to 57 respondents with accidental sampling technique. The analytical tool uses SPSS (Statistical Product for Service Solution). The results of the research conducted through a partial test showed that compensation had a positive but not significant effect and communication had a positive and significant effect. While the results through the simultaneous test show that compensation and communication have a positive and significant effect.